Effects of Hominis Placenta Herbal Acupuncture(HPA) on Menstrual Cramps - Weechang Kang; Jung-Hyo Cho; Yeon-Weol Lee; Chang-Gue Son; Chong-Kwan Cho; Hwa-Seung Yoo (Korean Pharmacopuncture Institute, 2005)
Purpose : The purpose of this study was to identify the effects of Hominis Placenta Herbal Acupuncture (HPA) combined with Acupuncture compared with Acupuncture therapy. Method : Data was collected from October 1st 2004 to February 28th 2005. A total of 8 women participated in this study. Of all subjects, 4 and 4 subjects were assigned to the experimental and the control group respectively. Subjects were treated three times a week. We used Visual Analogue Scale (VAS) for evaluating the effects of HPA. Result : There showed statistically boardline significance between the experimental group and control group (p=0.057). Conclusion : The results showed HPA has significant effects on menstrual cramps.